Socket shield: A case report - Kashinath C Arabbi; Mahantesha Sharanappa; Yashi Priya; Takshil D Shah; Shobha K Subbaiah (Wolters Kluwer Medknow Publications, 2019)
It is fairly common to remove a severely compromised tooth and provide rehabilitation by means of an implant. Resorption of alveolar bone after extraction resulting in loss of bone height and width is an unpleasant sequelae causing difficulty in implant placement. Few procedures have been promoted to attain the required bone height and width, such as guided bone regeneration socket preservation with the use of various graft materials and barrier membranes. The disadvantages of these techniques are some amount of ridge height loss and loss of buccal/facial, ridge contour. The socket shield technique is a new method where a buccal segment of root is retained as a shield, which aids in retaining periodontal ligament on buccofacial aspect. The implant is placed (immediate placement) lingual to this shield. This maintains the alveolar ridge height and buccofacial contour, thus providing superior aesthetics. This case report shows placement of an implant in upper anterior region using this technique.